Providing in RDBMSs the Flexibility to Work with Various Non-Relational Data Models (Global Journal of Computer Science and Technology, 2023)
The inability of pure relational DBMSs to meet the new requirements of the applications which have emerged on the web has led to the advent of NoSQL DBMSs In recent years significant progress has been made in integrating into relational DBMSs the features essentials for taking into consideration these new requirements which mainly concern flexibility performances horizontal scaling and very high availability This paper focuses on the features which can enable the relational DBMSs to provide applications with the flexibility to work with various non-relational data models while providing the guarantees of independence integrity and performance of query evaluation
Keywords: ANSI/SPARC architecture of the DBMSs’ schemata; database design and models; relational data model; non-relational data models; virtual databases